Graph Theoretic Models for RNA Secondary Structure - Ahrendt, Chris R.; Scanlan, McKenzie; Anderson, Nicole; Riehl, Manda (My University, 2017)
RNA forms bonds with itself and partially determines how the RNA functions. We investigate some models for this RNA secondary structure using a mathematical object called a matching. Some bonds are more likely than others based on how close two molecules are and which bonds are thermodynamically minimal. A number of different models have been created to approximate which matchings are likely to appear in RNA and which are not. One family of models, called the largest hairpin family, allows unlimited stem-loops but restricts the number of pseudoknots in the RNA secondary structure. We investigate the intersection of all largest hairpin family matchings.
Color poster with text, figures and diagrams.
Keywords: Posters; Mathematics; RNA secondary structure